The role of cell-free DNA in predicting colorectal cancer prognosis. (2nd January 2018) - Cao, Bo; Zhou, Xin; Yang, Wanli; Ma, Jiaojiao; Zhou, Wei; Fan, Daiming; Hong, Liu
ABSTRACT: Introduction : Colorectal cancer is a cancer of the digestive system with poor prognosis. Cell-free DNA has received much attention with its unique predominance, especially in colorectal cancer. Areas covered : This study has summarized recent advancements and challenges regarding cell-free DNA in predicting CRC prognosis. Furthermore, the authors make predictions on the potential developments concerning cell-free DNA in future prognosis prediction techniques. Expert commentary : Cell-free DNA has the value of predicting CRC prognosis as an important biomarke. Further clinical trials should be performed to promote translating cell-free DNA into clinical applications.